NOW THAT YOU KNOW, HOW DO YOU FEEL? - Mbatha, Khonzi; Blanche, Martin Terre (PINS-Psychology in Society, 2025)
De Vos, Jan (2012) Psychologisation in times of globalisation. London: Routledge. ISBN 978-0-415-68202-2 pbk. Pages xi + 162.